Pemberdayaan Ekonomi Masyarakat Melalui Pelatihan Make Up Di Jorong Ranah Sigading Nagari Laweh Selatan - Dewi, Ika Parma; Rahma, Yulia Azika; asril, Nurul Pratiwi Asril; Nopita, Levi; Yeni, Dhea Berliana Rahma; Nurcahyati; Hutabarat, Dini Hidayah (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2024)
Cosmetology is facial art that aims to beautify the appearance of the face, with the right make-up technique it can cover some of the flaws on the face, make the face look fresh and bright. The rise of bridal models with make-up in modern clothes encourages housewives and young women in education. By doing this cosmetology training, unemployed housewives and young women can spend time attending cosmetology training courses. After they master make-up they can open their own make-up salon business. Makeup skills are also used as future capital to help restart the family economy. The method used in cosmetology training is to impart theoretical and practical principles. Planning begins with an explanation of material regarding make-up with make-up techniques and then continues with a make-up demo with the mothers. The goal is to tell the participants how to start from start to finish; what materials and tools to use, and so on.